Islamisation of the Self: The International Islamic University Malaysia Experience - Ushama, Thameem (Advances in Social Sciences Research Journal, 2023)
This article presents a brief study of how the Centre for Fundamental Knowledge (now defunct) at the International Islamic University Malaysia (IIUM) accelerated the knowledge of its academics to benefit its students by exegetically comprehending the Qur’ān through weekly discussions. The article is divided into two sections. Ḥalaqah and ᶜIbādah Camps are two non-formal education initiatives for ‘Islamizing the Self’, covered in the first section. Even though the term ‘Islamising the Self’ was not used explicitly, these initiatives centred on cultivating moral and spiritual excellence, an integral part of ‘Islamising the Self”. The weekly Ḥalaqah sessions detail its operationalisation and the curriculum spread over four years. Under the ᶜIbādah camps, several themes included the concept of ᶜIbādah, Brotherhood, Islamic personality, social awareness and responsibility, daᶜwah (as a fundamental obligation), Islamic civilisation as a saviour, realising the Islamic ideals and social realities, and istiqāmah are analysed. The second section illustrates the ‘Islamisation of the Self’ by instilling various concepts and themes to be internalised and practised by students on campus and upon graduation as lifelong learning. It studies the qualities and characteristics of ᶜIbād al-Raḥmān, al-Insān al-Kāmil, and khalīfatullāh fi al-arḍ, the attribute of ulū al-albāb, the issue of tazkiyat al-nafs, al-nafs al-ammārah, al-nafs al-muṭma’innah, the culture of “say what you do,” the phenomenon of tijārah and anṣārullāh, the concept of al-birr and al-taqwā, themes of ḥubb al-Dunyā, amrāḍ al-qalb, al-falāḥ, amānah, shūrā, ibtilā’and miḥnah, wasaṭiyyah, utilising Arabic terms, a course on Philosophy of Islamic Ethics, deviant teachings, the phenomenon of sū’al-ẓann, unity and ummatism, and congregational prayer advocated to be applied by students from 1983 to 1990. Finally, the article ends with a conclusion and recommendations.